AGGRESSIVENESS AND THE INTENSITY OF PROVISIONING (ARTIFICIAL FEEDING) HANUMAN LANGURS AROUND JODHPUR (RAJASTHAN) - DEVI LAL; D L. S. RAJPUROHIT (The Bioscan, 2010)
A behavioural study in free-ranging Hanuman langur (Semnopithecus entellus) around Jodhpur (west Rajasthan) was conducted during 2008-2009. Different patterns of agonistic behaviour and aggressiveness in different langur groups were observed depending on the intensity of provisioning during the study period. The effects of artificial feeding were examined between two troops having minimum and maximum provisioning by local peoples. Results are based on focal animal sampling and ad libitum sampling of 17 adult females in the group Kailana II (low provisioning) and Mandore troops of the langur population of Jodhpur. The behaviour of their aggressiveness was observed. Mandore troop having high provisioning and more interacting with human population was observed to be more aggressive and play more agnostic interaction within and between two troops compared to low provisioned troops. Highly provisioned troop had high-intensity aggression (68.9%) and aggressiveness. In Mandore total 85 incident were observed when troop members play a major role in aggressiveness. Studies on the nature of changing the aggressiveness with the intensity of provisioning and or human interaction are essential for a basic understanding of the behavioral strategies that individual displays when faced with changing food rapidly. ,